Current and Investigational Therapeutics for Fabry Disease - Felis, Andrew (Kidney Int Rep, 2019)
Fabry disease (FD) is an X-linked lysosomal storage disease caused by a deficiency in the lysosomal enzyme α-galactosidase (α-GAL). This in turn leads to the buildup of globotriaosylceramide, resulting classically in progressive kidney disease, peripheral neuropathy, early-onset cerebrovascular disease, gastrointestinal symptoms, hypertrophic cardiomyopathy, arrhythmias, corneal whorls, and angiokeratomas. The diagnosis of FD relies on identification of a low α-GAL enzyme activity, identification of a genetic mutation, or histologic evidence of disease. With more than 900 mutations identified, there is phenotypic variability deriving from both mutational effects as well as the effect of skewed X-inactivation in females. Treatment of this disease has relied on intravenous replacement of the deficient enzyme with agalsidase α or agalsidase β. However, treatment options for some patients with FD have recently expanded, with the approval of migalastat, an oral molecular chaperone. In addition to chaperone-based therapies, there are several additional therapies under development that could substantially reshape treatment options for patients with FD. Four approaches to gene therapy, through both ex vivo and in vivo methods, are under development. Another approach is through the administration of α-GAL mRNA to help stimulate production of α-GAL, which is another unique form of therapy. Finally, substrate reduction therapies act as inhibitors of glucosylceramide synthase, thus inhibiting the production of GB-3, promise another oral option to treat FD. This article will review the literature around current therapies as well as these newer therapeutics agents in the pipeline for FD.